1997
DOI: 10.1016/s0735-1097(97)00068-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Bidirectional Cavopulmonary Shunt in Infants Less Than 6 Months Old

Abstract: Outcomes after BCPS in young infants are comparable to those in older infants and children. However, our current preference is to defer this procedure until after 2 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 15 publications
3
52
1
3
Order By: Relevance
“…23,24 Bradley et al 23 noted that lower systemic oxygenation at the time of preoperative cardiac catheterization as well as elevated pulmonary vascular resistance were significantly associated with death. Reddy et al 24 reported only 2 early postoperative deaths (out of 42 patients), both associated with poor oxygen saturation; 1 of 3 late postoperative deaths (out of 37 patients) was also associated with poor oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Bradley et al 23 noted that lower systemic oxygenation at the time of preoperative cardiac catheterization as well as elevated pulmonary vascular resistance were significantly associated with death. Reddy et al 24 reported only 2 early postoperative deaths (out of 42 patients), both associated with poor oxygen saturation; 1 of 3 late postoperative deaths (out of 37 patients) was also associated with poor oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…This approach reduces morbidity and mortality at the time of the Fontan procedure 1,2 and is well tolerated Several series suggest the median length of hospital stay (LOS) is 5–7 days and there are relatively few complications 38 . Despite the generally excellent results there are a number of preoperative risk factors associated with prolonged LOS, hospital death, or failure of the cavopulmonary circulation to provide adequate oxygenation and/or acceptable hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the current era, short-and mid-term outcomes after SCPC are quite favorable: 30 day operative mortality is as low as 0.7% [12]. Studies with longer follow-up report survival in [85% of patients [19,22,23]. However, ventricular function as a preoperative risk factor has not been examined closely in these studies, and the proportion of patients with significant ventricular dysfunction in each cohort has not been reported.…”
Section: Discussionmentioning
confidence: 97%